EFEKTIVITAS LARUTAN KAPUR DALAM MENURUNKAN KADAR FOSFAT PADA LIMBAH CAIR RSUD KOTA SEMARANG - Astuti, Wiwin Tipuk Dwi; Joko, Tri; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Hospital effluent phosphate levels Semarang exceed the quality standards set out in the Perda Jateng No. 5 Tahun 2012. High levels of phosphates can cause eutrophication and environmental degradation. Advanced treatment processes to reduce phosphate that coagulation and flocculation processes using a hydrated lime. This study aims to determine the effectiveness of a hydrated lime in reducing phosphate levels in waste water RSUD Kota Semarang. This type of research is quasi-experimental design with pretest and post-test. The population in this research that effluent waste water RSUD Kota Semarang and the sample consisted of 56 liters of effluent waste water. Data analysis using Kruskal-Wallis test. The results of the preliminary stage which is the optimum dose as big as 4% hydrated lime provides phosphate levels decrease by 45,65%. Variations dose of hydrated lime at an advanced stage treatment is equal to 0; 1; 2; 3; 4; dan 5 ml produce phosphate content with value 5,87 mg/l; 5,95 mg/l; 5,24 mg/l; 2,43 mg/l; 1,96 mg/l; and 1,12 mg/l. Effective dose 160 mg/l can reduce phosphate content to 1,96 mg/l to meet quality standards, a minimum doses of the hydrated lime is 3,9 ml/l and a maximum dose is 4,2 mg/l. Statistical analysis shows that there are differences of various dose meaningful addition of lime solution to decreased levels of phosphate waste water RSUD Kota Semarang. The results of this study show that the addition of lime solution can reduce levels of phosphate waste water RSUD Kota Semarang.